Disentangling the Contribution of Spatial Reference Frames to Executive Functioning in Healthy and Pathological Aging: An Experimental Study with Virtual Reality - Silvia Serino; Francesca Morganti; Desirée Colombo; Elisa Pedroli; Pietro Cipresso; Giuseppe Riva (Sensors, 2018)
A growing body of evidence pointed out that a decline in effectively using spatial reference frames for categorizing information occurs both in normal and pathological aging. Moreover, it is also known that executive deficits primarily characterize the cognitive profile of older individuals. Acknowledging this literature, the current study was aimed to specifically disentangle the contribution of the cognitive abilities related to the use of spatial reference frames to executive functioning in both healthy and pathological aging. 48 healthy elderly individuals and 52 elderly suffering from probable Alzheimer’s Disease (AD) took part in the study. We exploited the potentiality of Virtual Reality to specifically measure the abilities in retrieving and syncing between different spatial reference frames, and then we administrated different neuropsychological tests for evaluating executive functions. Our results indicated that allocentric functions contributed significantly to the planning abilities, while syncing abilities influenced the attentional ones. The findings were discussed in terms of previous literature exploring relationships between cognitive deficits in the first phase of AD.